Rhythm in Painting after Cézanne - Sieradzki, Simon (Curtin University, 2024)
Rhythm in painting involves a sense of temporality and movement formed, at least partly, by static material. The research for this study focuses on this dichotomy and the correlation between music, rhythm and painting. Walter Pater recognised that painting functions more like music, with Paul Cézanne pioneering this approach. This study investigates Cézanne’s influence to better understand rhythm and painting on an aesthetic and practical level and to explore how to take its creative potential for painting further.